Analysis of the Thinopyrum elongatum Transcriptome under Water Deficit Stress - Yongjun Shu; Jun Zhang; You Ao; Lili Song; Changhong Guo (International Journal of Genomics)
The transcriptome of Thinopyrum elongatum under water deficit stress was analyzed using RNA-Seq technology. The results showed that genes involved in processes of amplification of stress signaling, reductions in oxidative damage, creation of protectants, and roots development were expressed differently, which played an important role in the response to water deficit. The Th. elongatum transcriptome research highlights the activation of a large set of water deficit-related genes in this species and provides a valuable resource for future functional analysis of candidate genes in the water deficit stress response.